Colombia's experience with reductions in social security contributions and their effects on employment - Farné, Stefano (2013)
The government that took office in Colombia in August 2010 undertook a radical shift in labor market policy. The reasons for these changes are to be found, in large part, in the policy priorities set by the government that preceded it. It placed great emphasis on stimulating domestic and foreign investment, mainly through general tax exemptions and especially for the acquisition of capital assets. At the same time, the monthly social security contributions of workers increased significantly, with the aggravating factor that the tax component of these contributions also increased. Finally, the minimum wage grew gradually but steadily. In the broader macroeconomic context, the process of revaluation of the national currency, which has been going on for a decade, should be highlighted.